Portuguese textiles and garments : the future arrived earlier - Sá, Jorge A. Vasconcellos e (1993)
The crisis within the Portuguese Textile industry threatens the survival of a large number of manufacturing firms, and its importance can not be over emphasized due to its depth and the importance of this industry in Portugal. It accounts for nearly 30% of the employment in the manufacturing sector. The causes of the crisis can be explained in terms of two concepts : Value Added and End Markets. Based on these concepts, on the past performance of the industry and on its present competitive position, a most likely scenario was then drawn. The Portuguese textile industry is in between The Most Developed European Countries (more capital intensive) and the Developing Countries (more labour intensive). It produces average quality/prize products and don't control the marketing function. It can be expected that competition from Third World Countries will become more and more fierce. Unless the Government and firms join hands in a program which aims decisively at obtaining the three values added : control of the marketing function (to maintain the situation is having the products merely bought from them), move to high quality/price products (although facing the competition from other European countries), and a reduction in the firms financial costs, (that derive from high interest rates and the relative valuation of the portuguese currency) the future will show a textile industry playing a lesser important role than its present one in the portuguese economy. In such a case, a future which was long forecoming wiii finally have arrived.